2020
DOI: 10.1002/pc.25831
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of novel phosphonium bromide‐montmorillonite nanocompound and its performance in flame retardancy and dielectric properties of epoxy resins

Abstract: To enhance the flame retardancy of 9,10‐dihydro‐9‐oxa‐10‐phosphaphenanthrene‐10‐oxide (DOPO) on epoxy resins (EPs), by addition reaction with allyltriphenylphosphonium bromide (ATPB), a novel DOPO‐containing phosphonium bromide (DOPO‐ATPB) was synthesized and its structure was characterized by Fourier transform infrared (FTIR), 13C nuclear magnetic resonance (NMR), and X‐ray photoelectron spectroscopy (XPS). By intercalating DOPO‐ATPB into montmorillonite (MMT) layers and with the help of solvents, the interca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 41 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…Consequently, as the frequency increases, the polarizability of the composites decreases, leading to a reduction in the D k . Additionally, the dipoles in a state of relaxation can hinder the establishment of steering polarization, and cause a reduction steering polarization 28 . Hence, the reduction in the D f value of EPCE and EPCE/8DSF may be ascribed to a decrease in dipolar steering polarization, which leads to a reduction in the dissipation of electric field energy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, as the frequency increases, the polarizability of the composites decreases, leading to a reduction in the D k . Additionally, the dipoles in a state of relaxation can hinder the establishment of steering polarization, and cause a reduction steering polarization 28 . Hence, the reduction in the D f value of EPCE and EPCE/8DSF may be ascribed to a decrease in dipolar steering polarization, which leads to a reduction in the dissipation of electric field energy.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, as the frequency increases, the polarizability of the composites decreases, leading to a reduction in the D k . Additionally, the dipoles in a state of relaxation can hinder the establishment of steering polarization, and cause a reduction steering polarization 28. Hence, the reduction in the D f value of EPCE and EPCE/8DSF may be ascribed to a decrease in dipolar steering polarization, which leads to a reduction in the dissipation of electric field energy.As illustrated in Figure4, the D k and D f values of EPCE at 10 MHz are 3.78 and 0.01105, respectively, whereas the D k and D f values of EPCE/8DSF composite are 3.58 and 0.00744, respectively, representing a reduction of 5.29% and 29.95% compared to EPCE.…”
mentioning
confidence: 99%
“…Epoxy resin (EP) is a widely employed thermosetting polymer material. [9][10][11] Thus, the modification of EP has been addressed extensively, such as adding functional particles to improve the thermal conductivity, 12 electrical conductivity 13 and flame resistance, 14,15 adding CNTs, 16 nano-clays, 17,18 inorganic alumina, 19,20 graphene oxide, [21][22][23] functionalized aramid nanofibers (fANFs), 24,25 pyrolyzed carbon black, 26 and other hybrid fillers 27,28 to enhance its comprehensive mechanical properties. Our previous studies have shown that the aminated PPTA can significantly strengthen and toughen triglycidyl-p-aminophenol (TGPAP) epoxy resin and its carbon fiber composite, and having little effect on the T g of EP.…”
Section: Introductionmentioning
confidence: 99%
“…As a kind of inorganic filler, montmorillonite (MMT) has the advantages of small size, high thermal stability and high intercalation capacity [ 17 ], which has received special attention in the field of flame retardants [ 18 , 19 ]. MMT can generate SiO 2 and other substances to cover the surface layer during the combustion process, playing a role in protecting the underlying resin matrix from further damage [ 20 , 21 ]. Meanwhile, MMT can also help to reduce the release rate of smoke, heat, and toxic gases during the combustion process [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%